Searching for Growth and Development in Authoritarian Mexico : A Brief Tale of the NAFTA Commitment Device - Gonzalez Reyes, Alfredo (World Bank, Washington, DC, 2017)
Mexico’s pursue and implementation of the North American Free Trade Agreement (NAFTA) was a pro-growth policy strategy that deepened Mexico’s economic liberalization process at a time of crisis and macroeconomic stabilization. In that context, NAFTA constituted a commitment device to investment that ensured continuity to both the stabilization and the liberalization processes. NAFTA was possible for Mexico thanks to a new coalition between public and private elites that had recently gone through a deep transformation process themselves. After more than twenty years, NAFTA has significant results in terms of investment and levels and diversification of trade; however, the evidence on its impact in growth and development is mixed. The asymmetry of negotiation power between the United States and Mexico affected the agreement, but its final shape and implementation were impacted in important ways by Mexico’s political realities. Two examples of this: The highly hierarchical, camarilla-style line of command of the Mexican team derived in in controversial concessions and strategic mistakes in the areas of agriculture and financial services. Later, a corporatist, authoritarian regime induced a weak supplementary labor accord that can have had the potential of effectively promoting higher equity through strengthened workers’ rights and more democratic industrial relations.